Study on the Mitochondrial Genome of Sea Island Cotton (Gossypium barbadense) by BAC Library Screening - Ai-guo SU; Shuang-shuang LI; Guo-zheng LIU; Bin-bin LEI; Ding-ming KANG; Zhao-hu LI; Zhi-ying MA; Jin-ping HUA (Journal of Integrative Agriculture)
The plant mitochondrial genome displays complex features, particularly in terms of cytoplasmic male sterility (CMS). Therefore, research on the cotton mitochondrial genome may provide important information for analyzing genome evolution and exploring the molecular mechanism of CMS. In this paper, we present a preliminary study on the mitochondrial genome of sea island cotton (Gossypium barbadense) based on positive clones from the bacterial artificial chromosome (BAC) library. Thirty-five primers designed with the conserved sequences of functional genes and exons of mitochondria were used to screen positive clones in the genome library of the sea island cotton variety called Pima 90-53. Ten BAC clones were obtained and verified for further study. A contig was obtained based on six overlapping clones and subsequently laid out primarily on the mitochondrial genome. One BAC clone, clone 6 harbored with the inserter of approximate 115 kb mtDNA sequence, in which more than 10 primers fragments could be amplified, was sequenced and assembled using the Solexa strategy. Fifteen mitochondrial functional genes were revealed in clone 6 by gene annotation. The characteristics of the syntenic gene/exon of the sequences and RNA editing were preliminarily predicted.